HUMAN RIGHTS AND NATIONAL SECURITY: FRANCE IN SEARCH OF THE RESOLUTION OF THE MIGRATION CRISIS - N. V. Shmeleva (Vestnik MGIMO-Universiteta)
Given the influx of refugees into Europe, the migration problem is growing increasingly urgent in France and in the EU in general. Besides, if earlier the economic needs of the country were put at the center of solving immigration issues, now the government should also proceed from security considerations, since the main negative consequence of the migration policy conducted until recently is the growing threat to the security of citizens. The major challenge the French authorities are facing is maintaining security and social cohesion, with at the same time human rights observed and republican values respected. Addressing the migration challenge on the existing legal basis is getting more and more problematic. The article briefly analyzes the institutional and political constraints on the activities of the government, as well as the immigration policy of France, conducted since the arrival of Jacques Chirac, in 1995, to the presidency, to nowadays. The author, proceeding from the principles of historicism and using a systemic approach, shows that there had been an effective immigration policy to the extent that it was possible. However, the result was deplorable. Conclusion: the restrictions existing in France and other Western democracies do not allow to address the immigration challenge, to maintain order on their territories, while their populations feel increasingly insecure. The French leaders begin to understand that acting within the existing paradigm, it is not possible to overcome the migration crisis. So the governments of France, as well as other European countries, have to make a difficult choice, as a radical change in immigration policy may contravene the country’s republican values, while the continuation of the previous course risks weakening the ability to ensure the safety of citizens and preserve the national identity, as well as the republican model of a social welfare state. Recent actions in this area by President Emmanuel Macron show that the imperative of ensuring the security of its citizens is beginning to be seen as the main priority in the migration policy.